Chronic subdural hematoma associated with moyamoya disease - Takeuchi, Satoru (Asian J Neurosurg, 2014)
Chronic subdural hematomas (SDHs) associated with non-operated moyamoya disease are extremely rare. A 68-year-old woman underwent burr-hole surgery for a right SDH, which resolved completely. On day 3, however, the patient suffered cerebral infarction in the right parietal lobe. Cerebral angiography demonstrated total occlusion of the bilateral internal carotid arteries with transdural anastomoses via branches of the right occipital artery and middle meningeal artery, feeding the left parietal cortex. A branch of the right middle meningeal artery passed near the burr hole, but was preserved. The patient was diagnosed of moyamoya disease. We thought that the main cause of chronic SDH might be the disruption of transdural anastomoses. Furthermore, we also hypothesized that we might have coagulated the small vessels of the transdural anastomoses which were undetectable by postoperative angiography, and that cerebral infarction might occur.